Preeclampsia and gestational weight gain in the Norwegian Fit for Delivery trial - E. R. Hillesund (BMC Research Notes, 2018)
Abstract Objective Excessive gestational weight gain is linked to risk of preeclampsia, but it is not clear whether the association is causal. The purpose of this paper was to examine gestational weight gain in the Norwegian Fit for Delivery study among women who developed preeclampsia compared to those who did not, and to further explore associations between weight gain and preeclampsia by including data on body composition (bioimpedance) assessed in the last trimester of pregnancy. Results A total of 550 women were eligible for the study. Women who developed preeclampsia gained more weight than women who did not (difference 3.7 kg, p = 0.004), with a 3.5 kg difference in total body water observed in week 36 (p = 0.040). Adjusted for age, education, pre-pregnancy body mass index (BMI), randomization, and fat mass, a one kg increase in GWG was associated with 1.3 times higher odds of preeclampsia (OR: 1.31, 95% CI 1.15–1.49, p < 0.001). An independent inverse association between fat mass in week 36 and odds of preeclampsia was observed (OR: 0.79, 95% CI 0.68–0.92, p = 0.002). Given the observed difference in total body water, these findings point to excess fluid as the component driving the association between gestational weight gain and preeclampsia in the present study. Trial registration The NFFD trial has the Clinical Trials registration: clinicaltrial.gov NCT0100168